2010
DOI: 10.1177/1362361310363282
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of TeachTown: Basics computer-assisted intervention for the Intensive Comprehensive Autism Program in Los Angeles Unified School District

Abstract: Computer Assisted Instruction (CAI) has shown increased popularity recently and there are many studies showing promise for this approach for children with Autism Spectrum Disorders (ASD). However, there are no between-subject studies to date assessing the efficacy of CAI with this population. In this study, 47 preschool and K-1 students in ASD classrooms participated from Los Angeles Unified School District. TeachTown: Basics, a CAI program which also includes supplementary off-computer activities, was impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(75 citation statements)
references
References 22 publications
1
71
0
3
Order By: Relevance
“…While other studies mention anecdotal reports of generalization to real settings (Golan and Baron-Cohen 2006;LaCava, et al 2007;Golan et al 2010;Whalen et al 2010;Lacava et al 2010) or limited generalization to real settings in unpublished laboratory findings (Bernard-Opitz et al 2001). None of these studies have shown social skills generalization to a real setting and several call for further research to investigate it (Golan and Baron-Cohen 2006;LaCava et al 2007;Golan et al 2010;Tanaka et al 2010;Whalen et al 2010).…”
Section: The Current Studymentioning
confidence: 94%
See 1 more Smart Citation
“…While other studies mention anecdotal reports of generalization to real settings (Golan and Baron-Cohen 2006;LaCava, et al 2007;Golan et al 2010;Whalen et al 2010;Lacava et al 2010) or limited generalization to real settings in unpublished laboratory findings (Bernard-Opitz et al 2001). None of these studies have shown social skills generalization to a real setting and several call for further research to investigate it (Golan and Baron-Cohen 2006;LaCava et al 2007;Golan et al 2010;Tanaka et al 2010;Whalen et al 2010).…”
Section: The Current Studymentioning
confidence: 94%
“…Several published studies have evaluated the efficacy of computer or DVD video based interventions to enhance the social skills abilities of children with ASD (Bernard-Opitz et al 2001;Silver and Oakes 2001;Bölte et al 2002;Golan and Baron-Cohen 2006;LaCava et al 2007;Golan et al 2010;Tanaka et al 2010;Whalen et al 2010;Lacava et al 2010). These technology-based social skills interventions all leverage the affinity of students with an ASD for the predictable and animated environment of a computer game or video (Goldsmith and LeBlanc 2004).…”
Section: The Current Studymentioning
confidence: 96%
“…Additionally, the degree of program use was positively associated with the amount of improvement. Importantly, Whalen et al (2010) note that up to one third of the children with ASD were unable to master any of the lessons in the program. This suggests that CAI may not be appropriate for some children with ASD, especially when the programs do not allow for individualization that directly addresses their unique developmental level (Table 1).…”
Section: Receptive and Expressive Vocabulary Developmentmentioning
confidence: 98%
“…In a follow-up study conducted in a school district setting (Whalen et al 2010), children from ASD classrooms were randomized to a computer plus playbased or play-based alone condition to learn receptive and expressive language skills. The intervention lasted 3 months and was conducted for 20 min per school day.…”
Section: Receptive and Expressive Vocabulary Developmentmentioning
confidence: 99%
“…In the second part, an assistive learning system called LASAC is introducedthat serves an interactive Malayalam language learning assistive system for children with AS.Several comparative studies between traditional teaching methods and digital teaching methods have found that computer assisted programs were more effective in improving language as well as cognitive outcome measures of autistic children [8,9]. These studies also reveal that with the help of computer assisted and game like technologies, such children shows greater improvements in motivation and attentiveness [10].…”
Section: Introductionmentioning
confidence: 98%